Lanthanide-Doped Luminescent Nanophosphors via Ionic Liquids - Sharma, Rahul Kumar; Ghosh, Pushpal (Frontiers in Chemistry, 2021)
Lanthanide (Ln3+) ion(s)-doped or rare-earth ion(s) doped nanomaterials have been considered as a very important class of nanophosphors for various photonic and biophotonic applications. Unlike semiconductors and organic-based luminescent particles, the optical properties of Ln3+-doped nanophosphors are independent of the size of the nanoparticles. However, by varying the crystal phase, morphology, lattice strain etc. of the host materials along with making core-shell structure; relaxation dymanics of dopant Ln3+ ions can be effectively tuned. Interestingly, a judicious choice of dopant ions leads to unparallel photophysical dynamics like quantum cutting, upconversion, energy transfer, etc.. Recently Ionic Liquids (ILs) have drawn a tremendous attention in the field of nanomaterials synthesis due to their unique properties like negligible vapour pressure, non flammability and most importantly their tunability etc; for which these are oftenly called “green” and “designer” solvents. This review article aims providing a critical over-view about the latest developments in the ILs assisted synthesis of rare-earth doped nanomaterials and their subsequent photonic/biophotonic applications like energy efficient lighting, solar cell applications, photodynamic therapy, in vivo and in vitro bioimaging etc. This article will emphasize how luminescence dynamics of dopant rare-earth ions can be tuned by changing the basic properties of the host materials like crystal phase, morphology, lattice strain etc. which can be eventually tuned by various properties of ILs like cation/anion combination, alkyl chain length, viscosity etc. Last but not the least, different aspects of ILs like their ability to work as a templating agent, solvent, reaction partner and sometimes their use as a “three in one” in nanomaterials synthesis are highlighted along with various photoluminescence mechanisms of Ln3+- ion like up- and downconversion (UC and DC) etc.